Classification and Description of Pasture Lands of the Republic of Uzbekistan (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The study examines the classification and description of pasture lands in the Republic of Uzbekistan, focusing on their geographical distribution, vegetation characteristics, and monitoring mechanisms. Pastures constitute 46.6% of the country's land area, with 21.1 million hectares dedicated to livestock production, a key factor in regional socio-economic development. Despite their significance, systematic geobotanical research and pasture monitoring have been limited over the past three decades, resulting in data gaps that hinder effective resource management. The research identifies this deficiency as a core knowledge gap and proposes the establishment of continuous monitoring systems in accordance with the national “Law on Pastures.”The study employs a comparative analytical method using data from the Cadastre Agency and national reports (2019–2021), combined with ecological zoning principles. Pastures are classified into four major zones—desert, foothill, mountain, and high-mountain—each subdivided into lower and upper tiers based on altitude, soil type, and vegetation composition. Results reveal significant spatial disparities: Navoi Region accounts for 41.9% of total pastures, while Syrdarya, Andijan, and Fergana collectively represent less than 0.3%. Findings underscore the necessity of region-specific management strategies, emphasizing vegetation diversity as a key determinant of pasture productivity.The study concludes that implementing systematic land monitoring and digital cadastral mapping is vital for ensuring sustainable pasture use, ecological stability, and food security in Uzbekistan.